A Madurese Woman and Early-Matchmaking Tradition: Domination, Resistance, and Commodification in a Short Story “Sortana” by Muna Masyari - Erika Citra Sari Hartanto (SUAR BETANG, 2022)
Madura is one of amongst patriarchal societies which hold its tradition of arranged marriage in recent days. This study aimed to analyze the main character's representation as a Madurese woman whose life has been determined by her father and patriarchal society in Muna Masyari’s short story entitled “Sortana”. This study used a qualitative design, and data collection used close-reading. Feminist literary criticism, which is supported by Marxism theory, particularly commodification theory, was applied to reveal and analyze the position and values of a Madurese woman in the story. The results of this study showed that Muna Masyari portrays a Madurese woman who has to experience gender injustice related to an arranged marriage. The short story “Sortana” uncovers resistance by the main character toward men’s domination. In addition, the short story also reveals the act of commodification behind arranged marriage. AbstrakPenelitian ini bertujuan menganalisis representasi tokoh utama, seorang perempuan Madura yang hidupnya telah ditentukan oleh ayahnya dan masyarakat patriarki, dalam cerpen “Sortana” oleh Muna Masyari. Penelitian ini menggunakan metode kualitatif. Data dikumpulkan setelah melakukan pembacaan cermat. Kritik sastra feminis yang didukung oleh teori Marxisme, khususnya teori komodifikasi, diterapkan untuk mengungkap dan menganalisis posisi serta nilai-nilai perempuan Madura dalam cerita tersebut. Hasil penelitian menunjukkan bahwa Muna Masyari menggambarkan seorang perempuan Madura yang harus mengalami ketidakadilan gender karena pernikahan dini. Cerpen “Sortana” mengungkapkan tindakan resistansi yang dilakukan oleh tokoh utama terhadap dominasi laki-laki. Selain itu, cerpen tersebut juga menguak adanya tindakan komodifikasi di balik perjodohan dini.